Implementasi Peningkatan Kekuatan Otot Lansia Melalui Latihan Aktif Dan Pasif - Anggraeni , Dwi (ABDIMAS Madani, 2023)
Musculoskeletal disorders are one of the health problems that often occur in the elderly. The elderly suffer from musculoskeletal system declines, one of which is a decrease in muscle strength caused by a decrease in muscle mass. Decreased muscle strength that occurs in the elderly can lead to difficulties carrying out daily activities, so the elderly need help from others. One way to increase muscle strength is to do active and passive exercises. Purpose: to increase the knowledge of the elderly about the movement to increase muscle strength. Method: Community service is carried out using the demonstration method of active and passive exercise for 20 minutes. Prior to the demonstration, measurements of muscle strength and interviews were conducted. This activity was carried out on December 17, 2022, in Monggangt, with 20 elderly respondents who took part in community service. Results: Data on the characteristics of the respondents showed that there were 12 (60%) elderly women aged 60–66 years. Prior to the action, the elderly had a knowledge level of less than 13 (65%); after the action, the knowledge level was sufficient for as many as 12 (60%) and good for four (80%).Conclusion: There is an increase in knowledge in the elderly after demonstrating active and passive exercise movements in an effort to increase muscle strength.